Parametric investigation on the effect of nitrogen to reduce SF6 content in spark gap - Raj A.; Khaidir N.; Ishak S.; Ghani B.A.; Chakrabarty C.; Permal N.; Ahmad H. (American Institute of Physics Inc., 2023)
Almost all the MV and HV switchgears used by power utilities for interrupting faults are Sulphur Hexaflouride SF6 gas circuit breakers as this gas has the best dielectric properties to quench the onset of an arc in the event of fault. However due to strong dissociating properties of this gas when in contact with air that can release fluorine into the atmosphere, the Kyoto protocol has mandated to reduce the usage of SF6 in the future. SF6 is a greenhouse gas and it's about 3000 more severe than CO2. And that's the reason for replacing this gas. A close match in the quenching properties to SF6 that is now being intensively researched is nitrogen N2. This gas is considered to be an inert gas, and its release into the atmosphere has no harmful effects (except for asphyxiation - which can be easily handled with awareness). As the need for a replacement of SF6 becomes critical in the near future, the urgency to find the right gas is immediate. Hence the proposed work in this paper is to make a comprehensive parametric investigation of N2 gas in vacuum spark-gap. The spark-gap is chosen due to flexibility in changing the gap distance and easily be housed in vacuum. The parameters to be investigated are pure N2 and N2/ SF6 mix. The settling-time of the electrical break-down voltage and current are measured using voltage probe and Pearson probe. This time is paramount as it determines the speed of breaking the circuit. A faster breaking time ensures the safety of other HV equipment in the circuit. A comparative study between the various parameters will be conducted to obtain the best recipe (gas mix and gap distance) that gives the shortest settling time the breakdown using N2/ SF6/Mixture gas was successfully conducted and a Paschen curve has been established. 2017 Author(s).